THORNTHWAITE’S CLIMATE REGIONALIZATION FOR THE STATE OF TOCANTINS, BRAZIL - Souza, Fábio Henrique Morais de; Viola, Marcelo Ribeiro; Avanzi, Junior Cesar; Giongo, Marcos; Vieira Filho, Marcelo (Floresta, 2019)
Tocantins State faces a large-scale agricultural expansion. Thus, climate studies are essential for a better understanding of climate variability supporting agricultural and environmental planning. In this context, this study applies the climatic classification of Thornthwaite and develops a climate regionalization through geostatistical techniques, assessing the performance of the interpolators ordinary kriging (OK) and cokriging (CK). Data from 26 weather stations located in Tocantins State and surroundings were used. The variables of interest to climate regionalization, obtained by the climatic water balance, were mapped by geostatistical techniques. The results of cross-validation showed that ordinary kriging and cokriging performed well. The spherical and exponential semivariogram models obtained the best fit in 40% of the analyzes each, and the gaussian in 20%. The climatic classification of Thornthwaite applied to Tocantins State showed the presence of humid (B1), moist subhumid (C2), and dry subhumid (C1) climates. There were found three climatic regions: B1A’wa’: Humid, megathermal, with moderate winter water deficiency, and a temperature efficiency regime normal to megathermal , occurring in the western region of the state; C2A’wa’: Moist subhumid, megathermal, with moderate winter water deficiency, and a temperature efficiency regime normal to megathermal , occurring in the central region and extending from the north to the south of the state; and C1A’w2a’: Dry subhumid, megathermal, with large summer water surplus, and a temperature efficiency regime normal to megathermal , in the east and northeast of the state.